A comparative study of synechiae formation in endoscopic septoplasty with and without intranasal splints - Nagachaitanya, M.; Reddy, M. Santosh; Mohammadi, Uzma; Prathyusha, G. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Septoplasty is the treatment of choice for deviated nasal septum. Deviated nasal septum can be C shaped or S shaped leading to unilateral or bilateral nasal obstruction. Septal spur may also require surgery. Sometimes deviated nasal septum may block osteomeatal complex leading to chronic sinusitis. For the evaluation of nasal cavities preoperatively computed tomography (CT) paranasal sinuses and diagnostic nasal endoscopy is done. Diagnostic nasal endoscopy done after two weeks of surgery. The objective of the study is to compare the efficacy of intranasal splints in the prevention of nasal synechiae following septoplasty. Methods: 100 patients undergoing septoplasty under general anesthesia from March 2018 to March 2019 were enrolled. Patients with nasal septal deviation and aged between 18-50 years were included in the study. All surgeries were performed by consultant ear, nose and throat (ENT) surgeons under general or local anesthesia. Institutional ethical committee approval was obtained for the study. Informed consent was obtained from all patients. Patients with age under 18 years or over 50 years were excluded for the study. Results: Septoplasty with intranasal splints reduce the formation of synechiae in 48 patients. Conclusions: Usage of intranasal splints indicates a decrease in the postoperative formation of synechiae after septoplasty.